The New Zealand Civil Union Act: New Challenges for Private International Law - Campbell, Joanna (Victoria University of Wellington Law Review, 2006)
This article discusses private international law issues which arise as a result of the Civil Union Act 2004, which came into force in 2005. The author first discusses what kind of recognition New Zealand may extend to foreign unions, including both civil union type relationships and same sex marriages. This discussion considers recognition under the Civil Unions (Recognised Overseas Relationships) Regulations 2005, recognition as marriage and other possible avenues of recognition. This includes a consideration of currently recognised and unrecognised relationships, and the desirability of the current approach. It also includes a discussion of the issues surrounding the recognition of these types of relationships generally; for example, validity, status and public policy. The author then considers what kind of recognition the New Zealand civil union may receive in foreign jurisdictions.